Climate Extremes Walking Together: Evidence from Recent Compounding Climate Hazards after Remal - Ghosh, Surajit; Dawn, Arpan; Kour, Sneha; Mallick, Archita; Chowdhury, Anuva; Kundu, Kaushiki; De Sarkar, Kounik; Rahman, Md. Rayhanur; Sharma, Prashanti; Rajakaruna, Punsisi; Rahman, Md. Munsur; Nath, Arun Jyoti; et al. (Elsevier, 2025)
On May 26, 2024, Tropical Cyclone (TC) Remal made a devastating landfall along the coastal regions of India and Bangladesh. The sequence of devastating events began with prevailing heatwaves, followed by the cyclone’s landfall and subsequent heavy rainfall coupled with early onset of monsoon led to floods, landslides, and the resurgence of hot spells. It illustrates the complexity of managing such cascading effects of compound climate hazards. Multisource Earth Observation (EO) data with Google Earth Engine (GEE) was used to study the dynamics of Remal and its cascading impacts. IbTracks, INSAT-3D, GPM, Sentinel-1, and PlanetScope were involved in analyzing the cyclone's progression and impacts. Remal's slow progression extended the impact of the cyclone as it hovered over Bangladesh for more than 50 hours. As observed from the GPM data, the right side of the cyclone's path experienced more extensive and severe flooding than the left. Flood extent mapping using the Sentinel-1 data and Otsu thresholding depicted Jogipara, Assam in India and Jashore, Narail, and Khulna in Bangladesh as among the worst affected regions. Additionally, the early onset of the monsoon and the triggered cyclonic rainfall in the area led to landslides in Assam and Meghalaya during this period. The present study advocates the usage of multisource EO data and GEE for quick assessment of compound hazards started Remal. The study also highlights the need for a deeper understanding to develop a more robust district disaster management plan integrating EO data for actionable disaster risk reduction strategies for TC.